3D printing of shape memory alloy based smart structures - Khoo, Zhong Xun (2019)
Nickel titanium (NiTi) shape memory alloy is one smart material that has the capability to directly convert thermal energy into mechanical work. This unique property gives rises to shape memory effect and superelasticity. In order to fully utilise these two behaviours, NiTi needs to be processed into the different geometries for various applications. Nonetheless, the conventional manufacturing processes have several complications. Moreover, NiTi is not an easy material to process as well due to its compositional sensitivity and poor machinability. Thus, the full potential applicability of NiTi has not been achieved. To address these issues, one proposed solution would be to adopt Selective Laser Melting (SLM) to fabricate the NiTi parts. This new method of producing NiTi components is also known as 4D printing. The fabrication of NiTi via the SLM process not only contributes to solving the current problems encountered, it also allows complex NiTi smart structures to be produced directly for new applications. However, it is essential to first have the knowledge in fabricating functional SLM NiTi parts before manufacturing for actual applications. Furthermore, as compared to producing conventional metals through the SLM process, the fabrication of NiTi is much more challenging. Not only do the produced parts require a high density that leads to good mechanical properties, strict compositional control is needed as well for the SLM NiTi to possess suitable phase transformation characteristics. Therefore, in this thesis, the different SLM process parameters were first optimised, followed by the characterisation of the samples. Subsequently, the properties of the samples were enhanced through the implementation of repetitive scanning and post-process heat treatment. The SLM process parameters that were studied included the laser power, laser scanning speed, hatch distance and scanning strategy. These parameters were optimised and the produced SLM NiTi parts had low internal porosity, good geometrical accuracy, minimal oxidation and similar phase transformation characteristics as the NiTi powder. The small deviations in the internal porosity and transformation temperatures of the optimised single scanned samples have indicated the high repeatability of the SLM process. However, these samples demonstrated poor mechanical properties when subjected to tensile deformation. Multiple fractures were observed before the samples failed at a highest tensile strain of about 6%. Hence, repetitive scanning was implemented to enhance the properties of SLM NiTi. The results obtained from the repetitively scanned samples suggested that the laser absorptivity and heat conductivity of the materials before and after the first scan would significantly influence the final properties of the SLM NiTi. With carefully controlled repetitive scanning process, the fabricated samples demonstrated excellent properties. First, the samples exhibited comparable phase transformation characteristics as the raw NiTi powder used with high repeatability. Second, they displayed the capability to deform to 8% strain under the tensile mode without failure. Additionally, the samples have also demonstrated the highest magnitude of 5.11% transformation strain, with an average value of 4.61%. This scale of shape recovery was comparable to the conventionally-produced NiTi parts with a maximum transformation strain of about 6%. Nevertheless, the gap between the transformation strains of repetitively scanned samples and conventionally-made NiTi components indicated the possibility of further enhancing the shape memory properties of SLM NiTi. Therefore, post-process heat treatment was introduced to meet this objective. The results showed that the implementation of heat treatment had both positive and negative influences. A balance between these effects was needed to obtain an improvement in the shape memory responses of the repetitively scanned samples. It was observed that the samples subjected to heat treatment at 400 ˚C for a period of 5 minutes had higher transformation strain and percentage of shape recovery than the non-heat treated samples. The improvement in the shape memory properties was primarily due to the formation of a high density of fine Ni4Ti3 metastable precipitates. Nonetheless, increasing the heat treatment temperature to above 400 ˚C has resulted in overaging and further enlargement of the grain size. Consequently, degradations in the shape memory responses of the SLM NiTi samples were observed.